QUIZ, QUIZ, TRADE AS AN ALTERNATIVE THINK-PAIR SHARE STRATEGY TO IMPROVE THE SEVENTH GRADERS’ SPEAKING ABILITY IN TRANSACTIONAL TEXTS (RETAIN, 2017)
QUIZ, QUIZ, TRADE AS AN ALTERNATIVE THINK-PAIR SHARE STRATEGY TO IMPROVE THE SEVENTH GRADERS’ SPEAKING ABILITY IN TRANSACTIONAL TEXTS Denanda Pratiwi Putry English Education, Languages and Arts Faculty, State University of Surabaya pratiwidenanda@gmail.com Abstract The main goal of English Education is enable students to communicate in oral and written. Students’ speaking ability has to cover all supporting competences which are accent, grammar, vocabulary, fluency, and comprehension. Despite of being expected to master the competences, they still have difficulty in speaking, for instance, being unable to produce utterance fluently and confidently. Think-Pair-Share has been examined by several experts as a strategy to decrease speaking difficulty. Nowadays, Think-Pair-Share has been developed to become various kinds of strategies, one of which is Quiz, Quiz, Trade. It is believed that it can assist students to improve their oral skill. This study was done with the intention to know the significant differences of speaking ability between the experimental and the controlled groups. A pre-test was given to both groups at the beginning of the study while a post-test was done at the end of the study. The treatments were given to the experimental group only after the pre-test was done. All data were calculated by using SPSS 20. The calculation aimed to calculate the mean scores, standard deviations, homogeneity, and Independent t-test. In this study, it was found that the experimental group had better speaking ability rather than the controlled group. The calculation showed the mean score of experimental group is 73.89, however, the mean score of controlled group is 61.47. Further, after comparing the t-value (4.7) and t-table (1.67), the researcher concluded that there is a significant difference between the two groups. Additionally, to know the students’ speaking improvement of each supporting competences, the researcher compared the mean scores of the competences. The result was experimental group got higher scores in all supporting competence as mentioned previously. Therefore, Quiz, Quiz, Trade succeeded to give positive effect to students’ speaking ability. In a word, the Quiz, Quiz, Trade is effective to improve the seventh graders’ speaking ability in transactional texts. Keywords : Speaking, Think-Pair-Share, and Quiz, Quiz, Trade. Abstrak Tujuan utama dari pembelajaran Bahasa Inggris adalah memungkinkan siswa dapat berkomukasi secara lisan maupun tulis. Kemampuan berbicara siswa harus meliputi kompetetensi pendukung seperti seperti pengucapan, tata bahasa, pebendaharaan kata, kelancaran, dan pemahaman. Meskipun dianggap dapat mengusai seluruh kompetensi, mereka masih memiliki kesulitan dalam berbicara, seperti tidak bisa berbicara dengan lancar dan percaya diri. Think-Pair-Share telah diuji oleh beberapa ahli sebagai sebuah strategi untuk mengurangi tingkat kesulitan dalam berbicara. TPS berkembang menjadi berbagai macam Strategu salah satunya adalah Quiz, Quiz, Trade. Quiz, Quiz, Trade diyakini dapat membantu siswa dalam meningkatkan kemampuan berbicara mereka. Peneilitian ini dilakukan dengan tujuan untuk mengentahui perbedaan signifikan dari kemampuan berbicara antara grup eksperimen dan kontrol. Pre-test diberikan kepada kedua grup di awal penelitian sementara post-test dilakukan di akhir penelitian. Semua data dihitung menggunakan SPSS 20. Penghitungan bertujuan untuk menghitung skor rata-rata, standar deviasi, homogeneity, dan t-test. Pada penelitian ini, ditemukan bahwa grup eksperimen memiliki kemampuan berbicara lebih baik dari pada grup kontrol. Hasil penghitungan menunjukkan skor rata-rata grup eksperimen adalah 73.89 sementara skor rata-rata grup kontrol adalah 61.47. lebih jauh lagi, Setelah membandingkan nilai t (4.7) dan table t (1.67), peneliti menyimpulkan bahwa ada perbedaan signifikan dari kedua grup. Selain itu, untuk mengetahui peningkatan berbicara siswa, peneluti membandingkan skor rata-rata dari tiap kompetensi yang te;ah disebutkan sebelumnya. Jadi, penghitungan mengindikasikan bahwa Quiz, Quiz, Trade sukses memberikan dampak positif terharap kemampuan berbicara siswa. Singkatnya, Quiz, Quiz, Trade efektif untuk meningkatkan kemampuan berbicara siswa kelas VII pada teks transaksional. Kata kunci : Berbicara, Think-Pair-Share, dan Quiz, Quiz, Trade.